Inovação em serviços públicos: o caso Poupatempo - Teciano, Livia de Carvalho Gutierrez (2014)
This paper contributes to the study of Science, Technology and Society meanwhile analyses the innovation in public services, by applying concepts of bureaucracy and innovation to public institutions. For this, the study presents a discussion of the evolution process of science in society, presenting the concept of Weber's bureaucracy correlated to the concept of Schumpeter called "creative destruction." From this context, it is shown how competition leads to a process of construction and deconstruction of new products and processes, creating new technologies and methodologies that overlap the previous ones, in a continuous process of development. It also demonstrates how, in the context of the renovation of the State, public organizations need to be constantly innovating and seeking new ways of service delivery, to ensure citizens' satisfaction and, consequently, the legitimacy of its political actors. Finally, it is analyzed the concept of bureaucracy and "creative destruction" applied to public institutions through a brief explanation of the process of reforms in the public sector in the world and in more detail in Brazil. As an example of the innovative actions of public institutions, the case of Poupatempo Program of the Government of the State of São Paulo, showing in details its conception, structure and technological tools.